The sub-MIC selective window decreases along the digestive tract: determination of the minimal selective concentration of oxytetracycline in sterilised intestinal contents - Imazaki, Pedro Henrique; Voisin, Bertille; Arpaillange, Nathalie; Roques, Béatrice B.; Dordet-Frisoni, Emilie; Dupouy, Véronique; Ferran, Aude A.; Bousquet-Mélou, Alain; Bibbal, Delphine (Frontiers in Microbiology, 2024)
Introduction The administration of antibiotics can expose the digestive microbiota of humans and animals to sub-inhibitory concentrations, potentially favouring the selection of resistant bacteria. The minimal selective concentration (MSC) is a key indicator to understand this process. The MSC is defined as the lowest concentration of an antibiotic that promotes the growth of a resistant strain over a susceptible isogenic strain. It represents the lower limit of the sub-minimal inhibitory concentration (MIC) selective window, where resistant mutants can be selected. Previous studies focused on determining the MSC under standard culture conditions, whereas our research aimed to determine the MSC in a model that approximates in vivo conditions. Methods We investigated the MSC of oxytetracycline (OTC) in Mueller-Hinton broth (MHB) and sterilised intestinal contents (SIC) from the jejunum, caecum and rectum (faeces) of pigs, using two isogenic strains of Escherichia coli (one susceptible and one resistant to OTC). Additionally, the MIC of OTC against the susceptible strain was determined to assess the upper limit of the sub-MIC selective window. Results Our study took a novel approach, and the results indicated that MIC and MSC values were lower in MHB than in SIC. In the latter, these values varied depending on the intestinal segment, with distal compartments exhibiting higher MIC and MSC values. Moreover, the sub-MIC selective window of OTC in SIC narrowed from the jejunum to the rectum, with a significantly closer MSC to MIC in faecal SIC. Discussion The results suggest that OTC binds to digestive contents, reducing the fraction of free OTC. However, binding alone does not fully explain our results, and interactions between bacteria and intestinal contents may play a role. Furthermore, our findings provide initial estimates of low concentrations facilitating resistance selection in the gut. Finally, this research enhances the understanding of antimicrobial resistance selection, emphasising the intricate interplay between antibiotics and intestinal content composition in assessing the risk of resistance development in the gut.